0951 A Pilot Study For In-patient Screening Of Stroke Patients For Obstructive Sleep Apnea In A Community Hospital, And To Assess Follow Up Of Suspected OSA. (12th April 2019) - Fischer, Esther; Gupta, Divya; Suhan, Laura; Practictioner, Nurse; Siegel, Michele; Patel, Hemal; Bhat, Sushanth; Polos, Peter; Panezai, Spozhmy; Strauss, Sara; Mehta, Siddharth; Kirmani, Jawad
Abstract: Introduction: Obstructive sleep apnea (OSA) is a major risk factor for incident as well as recurrent stroke, and for increased mortality at 10 year follow up. Most hospitals do not routinely screen for OSA in the acute stroke population, potentially missing this important risk factor. With this quality improvement project, we aim to screen for OSA in the inpatient stroke population, and assess likelihood of referral of stroke patients to an outpatient sleep clinic or sleep study, within 6 weeks of discharge from the hospital. Methods: This is an ongoing study to screen all eligible patients who have been admitted to JFK Medical Center stroke unit, with MRI-proven acute ischemic stroke. The nurses take consent and screen patients for OSA using the STOP-BANG questionnaire. A score of >5 is considered at "high" risk. Patients are informed about their score and provided a prescription by the admitting physician, that refers them to an outpatient sleep clinic or a sleep study. The investigators do phone follow up of these patients to assess likelihood of such patients scheduling a sleep clinic/study appointment within 6 weeks after discharge from the hospital. Results: Between Oct 22 nd, 2018 to current, 178 patients were admitted to the stroke unit for symptoms suspicious of ischemic stroke. Ages ranged from 25 - 92 years (average 66.5 years). 86 patients (52.7%) were female. 24 patients met inclusion criteria of MRI-proven ischemic stroke. Of those, 3 patients consented to being screened for OSA. Of these, 2 had STOP-BANG scores above 5, and therefore qualified for referral to an outpatient sleep clinic. Conclusion: This ongoing quality improvement project aims to identify rates of referral for sleep evaluation, of stroke patients for who are at high risk for OSA. The ultimate goal of the project is to develop a network-wide protocol for screening of OSA in patients admitted for acute stroke, and establish practical methods for outpatient referral and diagnosis. Support (If Any)